Psychopathology, Dissociation and Somatic Symptoms in Adolescents Who Were Exposed to Traumatic Experiences - Luoni, Chiara; Agosti, Massimo; Crugnola, Sara; Rossi, Giorgio; Termine, Cristiano (Frontiers in Psychology, 2018)
The immediate and long-term consequences of children's exposure to traumatic experiences can be seen in a complex continuum, based first of all on the type of trauma. Children’s reactions to trauma may have different manifestations from the clinical picture of the PTSD, exhibiting dissociative, somatic, depressive or anxiety symptoms, and/or disruptiveness. We have enrolled 107 subjects, aged between 12 and 18 years, who consecutively referred for a psychiatric evaluation to the Child Neuropsychiatry Unit of the “Del Ponte” Hospital in Varese. All subjects underwent a clinical evaluation performed by infantile neuropsychiatrists. The battery of tests that was administered to patients included CGI and CGAS (filled out by the clinician), CBCL (filled out by parents), MMPI-A and TSSC-A (filled out by patients), and Wechsler scale. We found out that 35.5% of subjects had a mood disorder, 23.4% a personality disorder, 13.1% a psychotic disorder, 20.6% a post-traumatic stress disorder, while 26.2% were classified as other diagnostic categories (more frequently ADHD, DOP and conduct disorders). 58.9% of patients had at least one comorbidity. 33.6% of subjects also experienced a complex trauma. In multivariate logistic regression analyses, subgroup membership was collapsed to compare the single trauma and no trauma versus complex trauma group. Gender, age and affective disorders were generally unrelated to subjects', clinicians' and parents' scores. About subjects' self-assessment (MMPI-A Structural Summary Factors), complex trauma history was a statistically significant contributor to high scores on the Immaturity, Health Concerns, Familial Alienation and Psychoticism Factors, followed by presence of dissociative symptoms (except for Familial Alienation factor). Presence of dissociative symptoms, personality and psychotic disorder diagnosis was related to higher clinician impairment scores (CGI-S>4). These results reinforce available evidence that in trauma-exposed adolescents, the full burden of trauma, including other psychiatric diagnosis than PTSD, (such as affective, personality and psychotic disorders), dissociative and somatic symptomatology, is substantial and needs appropriate assessment and therapeutic interventions.